Analysis of Remedial Teaching Implementation in Merdeka Curriculum to Achieve High School Biology Learning Objectives - Shabrina Gifa Irsalina; Zulfiani (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
Remedial programs are an essential part of the learning process, designed to support students who have not yet achieved full mastery of specific material. In line with the principles of the Merdeka Curriculum, remedial teaching emphasizes flexibility and adaptability as corrective measures. This study aims to analyze the implementation of remedial teaching for Biology in grade XI at SMA Negeri 5 Depok, focusing on its role in helping students meet the learning objective achievement criteria, also known as Kriteria Ketercapaian Tujuan Pembelajaran (KKTP). This research uses a qualitative case study approach. Data were collected through structured interviews with students, Biology teachers, and the vice principal of curriculum, supported by observations and document analysis. The data analysis technique used was the Miles and Huberman method. The findings reveal that although teachers recognize the importance of remedial teaching, its implementation is often hindered by time constraints. As a result, remedial efforts are generally limited to reassessment activities rather than being integrated into regular instruction. This study suggests that teachers should incorporate remedial strategies into their lesson planning from the outset and consider using digital tools or alternative media to address time limitations and enhance instructional effectiveness.